Agulhas Current Meanders Facilitate Shelf‐Slope Exchange on the Eastern Agulhas Bank. Issue 7 (10th July 2018) - Malan, Neil; Backeberg, Bjorn; Biastoch, Arne; Durgadoo, Jonathan V.; Samuelsen, Annette; Reason, Chris; Hermes, Juliet
Abstract: Large solitary meanders are arguably the dominant mode of variability in the Agulhas Current. Observational studies have shown that these large meanders are associated with strong upwelling velocities and affect the shelf circulation for over 100 days per year. Here 10‐year time series from two ocean general circulation models are used to create a composite picture of the Agulhas Current and its interactions with the shelf circulation in meandering and nonmeandering modes. Both models show good agreement with the size, propagation speed, and frequency of observed meanders. These composite meanders are then used to examine the response of shelf waters to the onset of large meanders, with the use of model output enabling the dynamics at depth to be explored. Results show a composite mean warming of up to 3°C of depth‐averaged temperature along the shelf edge associated with an intrusion of the current jet onto the shelf driven by an intensification of the flow along the leading edge of large meanders. However, this intensification of flow results in cooling of bottom waters, driving cold events at the shelf break of <10°C at 100 m. Thus, the intensification of the current jet associated with large meander events appears to drive strong up and downwelling events across the inshore front of the Agulhas Current, facilitating shelf‐slope exchange. Plain Language Summary: Agulhas Current meanders are some of the largest events that take place in the Agulhas Current system. They have a large impact on the shelf circulation and are important for the life cycle of several marine species. Here two ocean models, as well as satellite observations, are used to examine how meander events change the way in which the Agulhas Current interacts with the continental shelf of southeast Africa. It is found that meanders influence the pathways by which water is upwelled from below the Agulhas Current up onto the shelf, thus influencing the supply of nutrients to the shelf ecosystem. Key Points: Agulhas Current meanders drive upwelling events and have an influence on shelf‐slope exchange Large meander events are associated with warm intrusions at the shelf edge and cooling at depth Changes in bathymetry cause different meander‐driven upwelling regimes along the Agulhas Current